On coefficients estimate for subclasses of bi-univalent functions defined by Ruscheweyh derivative operator - Jassim, Kassim A.; Hussein, Adnan Aziz (Iraqi Journal of Science, 2025)
This paper presents two subclasses of analytic and bi-univalent functions associated with the Ruscheweyh derivative operator to investigate the bounds for  and where  and  are the initial Tayler-Maclaurin coefficients. The current results would generalize and improve some corresponding recent works. Additionally, in certain cases, our estimates correct some of the existing coefficient bounds.